2017
DOI: 10.1038/s41467-017-00396-9
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 antagonizes TGF-β signaling and inhibits breast cancer metastasis

Abstract: Distant metastasis is the main cause of breast cancer-related death; however, effective therapeutic strategies targeting metastasis are still scarce. This is largely attributable to the spatiotemporal intratumor heterogeneity during metastasis. Here we show that protein deacetylase SIRT7 is significantly downregulated in breast cancer lung metastases in human and mice, and predicts metastasis-free survival. SIRT7 deficiency promotes breast cancer cell metastasis, while temporal expression of Sirt7 inhibits met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
170
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(185 citation statements)
references
References 70 publications
11
170
0
4
Order By: Relevance
“…Increasing evidence has indicated that EMT promotes breast cancer progression. Oncogenic pathways such as IL‐6/Stat3, TGF‐β/Smad3, Wnt and Notch are implicated in EMT‐associated breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has indicated that EMT promotes breast cancer progression. Oncogenic pathways such as IL‐6/Stat3, TGF‐β/Smad3, Wnt and Notch are implicated in EMT‐associated breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven Sirtuin members, SIRT7 has remained the least understood. Only a handful of deacetylation targets have been reported, including p53, NRF1, GABP-␤1, H3K18ac, PAF53, U3-55K, and Smad4 (5)(6)(7)(8)(9)(10)(11). SIRT7 may have many more potential substrates according to a study using stable isotope labeling by amino acids in cell culture (SILAC)-coupled quantitative MS (12).…”
mentioning
confidence: 99%
“…It also selectively deacetylates H3K18Ac at the promoters of a network of genes with links to tumor suppression (6). Interestingly, SIRT7 is reported to be significantly down-regulated in breast cancer lung metastases in humans and mice and predicts metastasis-free survival (11). Much more remains to be explored regarding the role of SIRT7 in tumor progression.…”
mentioning
confidence: 99%
“…Tumor metastasis is usually associated with abnormal expression of cytokines, especially CXCL12 [42][43][44][45][46], VEGF [47,48], IL1β [49,50], and IL6 [51,52], while CAFs can promote tumor growth and invasion via a plethora of active factors [53]. We therefore checked these specific cytokines in different cancer cells with the presence or absence of different NF-CMs.…”
Section: Discussionmentioning
confidence: 99%